Analisis Semiotika Visual Poster Konser Bts “Bang Bang Con: The Live” - Newahyu Jamalika Shintia; Fuji Astutu; Ardipal Ardipal; Indrayuda Indrayuda (CV. Publikasi Indonesia, 2026)
Glue abuse as an addictive substance among adolescents and marginalized communities is a social and health problem that requires comprehensive policy interventions. This paper aims to formulate strategies to counter glue abuse through a regulatory approach, distribution control, strengthening of the social environment, enforcement of sanctions, and rehabilitation. The method used is a policy analysis based on a normative review of laws and regulations related to public health and social rehabilitation, accompanied by the formulation of an implementation mechanism at the local government level. The results of the study show that the issuance of regional regulations/regional head regulations regarding sanctions for distributors, sellers, and consumers, as well as the implementation of a “one-tap” distribution system, can restrict access and suppress the circulation of glue. Environmental strengthening is carried out through the improvement of public facilities, the initiation of economic activities in vulnerable areas, and joint patrols. The enforcement of administrative and social sanctions, the provision of rewards and punishments for regional apparatus, the establishment of complaint channels, and the socialization of P4GN strengthen the preventive effect. On the curative side, the establishment of permanent rehabilitation facilities based on health and social regulations is a prerequisite for sustainable recovery. With the integration of prevention, enforcement, and rehabilitation, this policy has the potential to reduce the prevalence of glue abuse while enhancing public health protection at the regional level.